Establishing a Goat Community-Based Breeding Program in Mali - Rekik, Mourad; Dione, Michel; sow, ahmadou; Sacko, Idrissa; Tebourbi, Ons; Getachew, Tesfaye; Rischkowsky, Barbara; Haile, Aynalem; Marshall, Karen (International Livestock Research Institute, 2023)
Throughout history, the practices of livestock husbandry have been evolving with the aim of improving animal production to meet the changing needs and preferences of consumers. Among these practices, breeding has played a significant role in achieving the above-mentioned objectives. Breeding involves the selection of animals with the best traits, intending to preserve and improve desirable and heritable qualities in the next generations. This practice has been enhancing the genetic components of livestock, particularly sheep and goats, and, consequently, optimizing their productive potential. However, “classic” breeding programs currently face challenges such as high operational costs, the spread of specific animal diseases, and objectives mismatch. Therefore, effectively addressing these issues requires strategic and innovative approaches. Community-Based Breeding Program (CBBP) is a participatory, decentralized, and low-cost genetic improvement strategy for small ruminants. This strategy was firstly developed by ICARDA, in partnership with the International Livestock Research Institute (ILRI), and the Austrian University of Natural Resources and Life Sciences (BOKU), and it is intended to be put in place by communities depending on farmers’ objectives and capacities. CBBP has been first implemented in Ethiopia since 2009, in partnership with national actors, namely the Ethiopian National Agricultural Research System (ENARS), with the aim to improve small ruminants’ performances and increasing their productivity in low-income communities and is now being up scaled in Ethiopia and abroad. At the current stage, CBBP is being progressively implemented in Mali under CGIAR’s initiative “Sustainable Animal Productivity for Livelihoods, Nutrition and Gender inclusion (SAPLING)”, having ICARDA, ILRI collaborating with several public, private and professional partners in the country, namely Institut d’Economie Rurale (IER), Farmers’ Associations, National Association for Mandated Veterinarians (ANAVEM), Collective of Veterinarians of Mali (COVEM), Council of Barouéli, Regional Department of Animal Production and Industries of Ségou (DRPIA), Local Service of Animal Production and Industries of Barouéli (SLPIA), Regional Veterinary Services Department of Ségou (DRSV), Malian Association for the Promotion of the Sahel (AMPROS), Veterinary Sector of Barouéli (SV), University of Ségou - Faculty of Agronomy and Animal Medicine (US/FAMA), Tabital Pulaaku International, Union of Cooperative Societies of Breeders of Tamani (USCET), and Livestock - Meat Interprofession (URF Bétail-Viande). Essential to a full adoption and prior to field implementation of CBBP, a workshop was co-organized by ILRI and ICARDA with the purpose of bringing together all involved partners for the co-designing of this innovative approach, yet new to Mali for the genetic improvement of small ruminants in low-input, small holder goat raising farms in the district of Ségou. Subsequently, the on-ground implementation of the goat community-based breeding program took place in two villages. This included activities such as animal identification, baseline data collection, and the identification and practical training of enumerators and experts. 5